Transnational narratives: father-child separation from the perspective of migrant men's children in Ecuador. (1st September 2020) - Verdezoto, Jesenia; Llanes, Veronica
ABSTRACT: Multiple studies have explored the impact of international migration on family members. Nonetheless, scant attention has been given to the experiences of children who stay in the home country. This paper addresses this gap in the transnational family life literature by exploring father-child separation from the viewpoints of children in the country of origin. This is key to understanding the implications that separation has on the family's well-being, thus providing a broader assessment of the effects of international migration. Through a qualitative study based on interviews and field observations, we seek to obtain a wider vision of the context in which the transnational father-child relationship evolves and understand how the children's perception of the separation varies according to it. We can accomplish this by choosing three locations that are home to pioneer migrants in Ecuador, which have the highest rates of international migration. Qualitative data was collected from migrant men's children in Biblián, Sígsig, and Calderón. Most of the migrant fathers, except for one, were undocumented at the time of fieldwork. Overall, we argue that although transnational fatherhood and experiences should not be assumed to be fixed but influenced by context, father-child separation does have implications, particularly, for boys.